Health costs of pesticide use in a vegetable growing area, central mid-hills, Nepal - Atreya, Kishor (Himalayan Journal of Sciences, 2007)
This pilot study estimated the health costs resulting from pesticide-related acute health symptoms in a mid-hill vegetable growing area of Nepal. Farmers reported up to 13 acute symptoms due to the use of pesticides. Using the averting cost approach, on average a farmer spent NR 119 (US$ 1.58) annually for safety gear (at the time of study, NR 75 equaled US$ 1). Using the cost-of-illness approach, the total annual household expenditures due to the use of pesticides ranged from NR zero to NR 4451, with an average of NR 1261. Similarly, household willingness to pay (WTP) for safer pesticides ranged from as low as NR 1500 per year to as high as NR 50,000. Himalayan Journal of Sciences 3(5) 2005 p.81-84